Bispecific engineered antibody domains (nanoantibodies) that interact noncompetitively with an HIV-1 neutralizing epitope and FcRn. - Rui Gong; Yanping Wang; Tianlei Ying; Dimiter S Dimitrov (PLoS ONE)
Libraries based on an isolated human immunoglobulin G1 (IgG1) constant domain 2 (CH2) have been previously diversified by random mutagenesis. However, native isolated CH2 is not very stable and the generation of many mutations could lead to an increase in immunogenicity. Recently, we demonstrated that engineering an additional disulfide bond and removing seven N-terminal residues results in an engineered antibody domain (eAd) (m01s) with highly increased stability and enhanced binding to human neonatal Fc receptor (FcRn) (Gong et al, JBC, 2009 and 2011). We and others have also previously shown that grafting of the heavy chain complementarity region 3 (CDR-H3 (H3)) onto cognate positions of the variable domain leads to highly diversified libraries from which a number of binders to various antigens have been selected. However, grafting of H3s to non-cognate positions in constant domains results in additional residues at the junctions of H3s and the CH2 framework. Here we describe a new method based on multi-step PCR that allows the precise replacement of loop FG (no changes in its flanking sequences) by human H3s from another library. Using this method and limited mutagenesis of loops BC and DE we generated an eAd phage-displayed library. Panning of this library against an HIV-1 gp41 MPER peptide resulted in selection of a binder, m2a1, which neutralized HIV-1 isolates from different clades with modest activity and retained the m01s capability of binding to FcRn. This result provides a proof of concept that CH2-based antigen binders that also mimic to certain extent other functions of full-size antibodies (binding to FcRn) can be generated; we have previously hypothesized that such binders can be made and coined the term nanoantibodies (nAbs). Further studies in animal models and in humans will show how useful nAbs could be as therapeutics and diagnostics.